Implementation of Digital Storytelling to Increase Student Learning Interest in Prophet's Hijrah Material in Grade 5 - Mustain, Mustain (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study describes the implementation of digital storytelling in teaching Islamic Cultural History (SKI) material on the Hijrah of the Prophet Muhammad SAW in grade 5 at Madrasah Ibtidaiyah Da'waturrosyidin. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, then analyzed using the Miles & Huberman and Saldana models. The Research results indicate an increase in students' learning interest across three indicators. Enthusiasm increased from 11 to 17 students (5A) and from 12 to 15 students (5B). Active engagement rose from 10 to 17 students (5A) and from 9 to 15 students (5B). Participation was evident from 16 students (5A) and 15 students (5B) who dared to give presentations, with an additional six students (5A) and six students (5B) interacting. Interviews with students and parents reinforced that learning with digital media is more interesting, easier to understand, and fosters a spirit of learning. This study confirms that digital storytelling is compelling in increasing interest in learning SKI at the Madrasah Ibtidaiyah (MI) level. However, it is limited to grade 5 and the material on the Prophet's Hijrah.